Pregnancy outcomes of placenta accreta spectrum with and without previa - Nahid Javadifar; Nahid Shahbazian; Mitra Tadayon; Maryam Dastoorpour (Mashhad University of Medical Sciences, 2022)
Introduction: Abnormal adhesion of placenta is one of the complex problems of gynecology and obstetrics and is considered life-threatening for mother and fetus. The present study was performed aimed to compare the pregnancy outcomes in placenta accreta with and without previa. Methods: In this analytical-comparison study, the medical records of 50037 women who had referred to Imam Khomeini Hospital in Ahvaz for delivery in 2015-2019 were examined for the diagnosis and recording of abnormal placental adhesions. A total of 172 patients were confirmed with a definite diagnosis of abnormal placental adhesions that they were divided into two groups of accreta (n=95) and accreta with previa (n=7) for evaluation and comparison. Data were analyzed by SPSS (version 24) and Chi-square, T-test, and Man-Whitney test. P<0.05 was considered statistically significant. Results: There was no significant difference between the two groups in terms of number of pregnancy (P=0.884), number of cesarean (P=0.771), history of abortion (P=0.384), and gestational diabetes (P=0.824). Antenatal bleeding in accreta-privia group was 2.43 times of accreta group (OR: 2.34, 95% CI: 1.22-45, p=0.009) and there was significant difference between the two groups. No significant difference was observed between the two groups in the frequency of hysterectomy, percentage of blood transfusion, admission to ICU and the units of used blood, but cystostomy in previa-accreta group was 2.2 times to accreta group (P=0.027). There was significant difference between the two groups in terms of gestational age at birth (p=0.004), birth weight (p=0.054), and percentage of preterm delivery (P=0.015); so that gestational age and birth weight were significantly lower in the accreta-previa group. Conclusion: In both groups, accreta and accreta with previa were similar risk factors, but the needs for cystostomy and preterm delivery was significantly more in the accrete-previa group.